Effectiveness of auriculotherapy in hypogalactia - Soberao Rodríguez, Lidiana; Ramos Padilla, Kenia; Blanco Fuentes, Rosa Marila; Martínez Suarez, Roxana (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: breast milk intake produces a nutritional advantage in the baby. Worry, anxiety, lack of confidence and lack of support jeopardize the continuity of breastfeeding. Auriculotherapy is a method that consists in the use of ear points for preventive, diagnostic and therapeutic purposes.Objective: to evaluate the effectiveness of auriculotherapy in the treatment of hypogalactia in postpartum women attended at the Maternal-Child Block of the General Teaching Hospital “Abel Santamaría Cuadrado”, in the period 2022- 2023.Methods: a descriptive, longitudinal and prospective study was carried out, with a universe: 6767 and the sample: 86 puerperal women with hypogalactia, selected by non-probabilistic intentional sampling. Theoretical, empirical and descriptive statistical methods were used, by means of absolute and relative percentage frequencies.Results: the predominant age group was 22-30 years (39.5 %), pre-university level (61.6 %), marital status (51.2 %), professional occupation (25.6 %). Patients with Qi and Xue kidney and heart failure (86 %) were predominantly aged 31-39 years (33.8 %), the most frequent risk factor was stress and anxiety (66.3 %), and Qi and Xue kidney and heart failure was the syndromic diagnosis with the best response to treatment (74.3 %). After treatment, 73.3 % of the sample did not present hypogalactia.Conclusions: Auriculotherapy as a treatment for hypogalactia proved to be effective since it helped stimulate milk production, which demonstrates the feasibility, safety and speed of treatment with this natural therapy.